RELATIONSHIP BETWEEN PROFESSIONAL MOBILITY AND COMPETENCIES IN PREPARING FOR THE FUTURE QUALIFIED WORKERS - Sushentseva Л.Л. (Pedagogy of Higher and Secondary Education, 2022)
In article he auhor opens iportance preparanions professionally mobile qualiied worker on the baris of interrelation of professional mobility and competence.